A Means of 'Escape'? British Jewry, Communism, and Sport, 1920–1950. Issue 2 (2015) - Dee, David
Abstract : Between 1920 and 1950, a large number of British Jews took up sports and recreation within the Communist Party of Great Britain (CPGB). As members of the Young Communist League (YCL) and the British Workers' Sports Federation (BWSF), Jews engaged in sporting and recreational activities designed to promote communist policy and fraternity and act as a contrast to the commercialism of 'bourgeois' sports. Drawing on a broad array of archival and oral history materials, this article documents the growth and nature of Jewish participation in British 'communist' sport and leisure. It focuses on two aspects of this involvement. First, it illustrates that sports and socializing often proved to be a key factor in drawing Jews to communism and became a central aspect of a large number of young Jews' 'communist' lifestyles. Many young Jews participated in the movement mainly because it offered the chance to ramble, camp, cycle, dance, or play table tennis. Second, the article demonstrates that involvement in communist sport and recreation exerted an important impact on Jewish ethnicity. Communist sport catalysed many young Jews' estrangement from their elders by giving them an 'escape' route from their immigrant identities and helping them form new lifestyles, relationships, and characters.